Hermitian and Non-Hermitian Dirac-Like Cones in Photonic and Phononic Structures - Luo, Jie; Lai, Yun (Frontiers in Physics, 2022)
Accidental degeneracy plays an important role in the generation of novel band dispersions. Photonic structures that exhibit an accidental Dirac-like conical dispersion at the center of the Brillouin zone can behave like a zero-index material at the Dirac-point frequency, leading to a number of unique features, such as invariant phase in space, wave tunneling, photonic doping and anti-doping, etc. Such a phenomenon has been explored in on-chip structures or three dimensions recently. The introduction of non-Hermiticity into the system via loss or gain could transform the accidental Dirac-like cone into a spawning ring of exceptional points, a complex Dirac-like cone or other unique dispersions. Similar Dirac-like cones and related physics are also observed in phononic structures. This review presents an overview of the accidental-degeneracy-induced Dirac-like cones at the center of the Brillouin zone in both photonic and phononic structures, including the fundamental physics, effective-medium description and experimental demonstration, as well as current challenges and future directions.